The Effectiveness of Supportive Group Therapy to Reduce Impact of Stigma and Burden of Family Members of Schizophrenia Patients in Lampung Province, Indonesia - Lestari, Arena; Hussain Habil, Mohamad; Hashim, Faridah (Riviera Publishing, 2022)
Stigma and burden from family could be reduce if they have support from other family with the same problem. Supportive group therapy would be able to help family facing stigma and burden. The aim of this study was to explore the impact of stigma and burden on family members the care of schizophrenia patients with supportive group therapy. A mixed-methods exploratory sequential design was used which comprised of the qualitative data using focus group discussion with 14 participants and quantitative data using questionnaire to assess stigma, subjective burden and objective burden to 120 participants. The findings of stigma experience there are three main themes identified; concealment of illness, perceived devaluation, and social withdrawal. Five themes were found; emotional and physical health, interpersonal family relationship, loss of expectation, religion and spirituality as subjective burden and six themes was identified objective burden: financial, disruption of routine family activities, disruption of family leisure, disruption of family interaction, effect of physical health and effect of mental health. As for quantitative findings, after intervention the mean score of the stigma of family after three times repeated measurement decrease to 30.93 with p value = 0.00, for subjective burden score 154.06 with p value = 0.00 and for objective score burden was 14.53 with P value = 0.00. Supportive group therapy for family members of schizophrenia patients effective to reduce stigma and burden, several recommendations to propose this model to become one of therapy for family with schizophrenia as a program for mental health area.